Common Currency, Common Market? - Richard Friberg (Hungarian Academy of Sciences, Institute of Economics, 2003)
Does the common currency promote goods market integration within the EMU? We argue that such an effect is likely, but that the mechanism typically proposed lover costs of arbitrage because of increased price transparency is likely to be of minor importance. Instead we sketch a duopoly model which stresses that lover possibility of future real exchange rate variability lowers the option value of being able to price discriminate. The euro would promote market integration because it is less valuable for firms to segment markets. In addition we argue that fairness concerns and less risk associated with third party arbitrage may be potentially important.
Keywords: F13; F15; F41; L40; 330; exchange rate pass-through; law of one price; EMU; price discrimination; price transparency; real options